PENGARUH KUANTITAS PENAWARAN SAHAM, NILAI PENAWARAN SAHAM, UMUR PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP RETURN AWAL DAN RETURN 15 HARI SESUDAH IPO TAHUN 2010-2012 - DIAN EKA PUTRI, SARAH (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: This research aimed to examine the influence of financial variables (quantity of the share offering, value of the share offering, and firm’s size) and non-financial variables (firm’s age) in the prospectus on initial return and 15 days return after Initial Public Offering (IPO). The sample for this research are 60 companies listed on IPO from 2010-2012 through Indonesia Stock Exchange. The result of the regression analysis indicates that only the value of the share offering variable that significantly influence initial return and 15 days return after IPO negatively, it means that the higher of value of the share offering make smaller initial return and 15 days return after IPO. Variables quantity of the share offering, firm’s age, and firm’s size fail to show significant influence to initial return and 15 days return after IPO. Keywords: initial return, 15 days return after IPO, quantity of the share offering, value of the share offering, firm’s age, firm’s size.